TINJAUAN YURIDIS EKSEKUSI MATI UNTUK WARGA NEGARA ASING DAN KAITANYA DENGAN HUBUNGAN INTERNASIONAL INDONESIA DENGAN NEGARA LAIN - Wulandari, Natalia Desi; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The death penalty as one of the main criminal contained in article 10 of the Code of Penal always been an endless debate to this day. Others argue the pros against the death penalty and many cons. Especially it concerns the implementation to foreign nationals, where many countries that do not agree with the death penalty, particularly the socialist countries. Most of the socialist countries abolished the death penalty on the grounds of protection of human rights, according to the UN declaration of 1975 on guarding everyone from the tortured or treated or punished in a cruel, inhuman and debased. Moreover.The objectives to be accomplished author in this study are to determine the procedures for the execution of foreign nationals, to know the reaction of the countries in the world to die for the execution of foreign nationals in Indonesia and to determine the effectiveness of the death penalty in the world. This study is a normative legal research, the research uses the literature study will be concluded so deductively. Namely the conclusion initiated by the things that are common to the things that are special.While the results of this research will explain about the definition of a link between the death penalty and executions of human rights in relation to Indonesia as a state of law and the status of the death penalty in Indonesian positive law and historical procedures for executions in the world. Besides the core of this study is that the authors will explain the procedure of execution for foreign nationals in Indonesia are regulated in Presidential Edict No. 2 of 1964 which is also listed in the State Gazette No. 38 of 1964 on the Procedures for Execution of Death in the Region General Court and the Court military, the reaction of countries in the world, especially Australia, Brazil and France .Keywords: Execution Dead, foreigners, International Relations